Workplace violence against nurses and the challenge of underreporting: A literature review - Serlina, Serlina; Melastuti, Erna; Wahyuningsih, Indah Sri (Palembang MediRose Publisher, 2025)
Background: Workplace violence (WPV) against nurses is a critical global concern that negatively affects nurse well-being, professional performance, and patient safety. Despite its widespread occurrence, WPV is consistently underreported. This persistent gap between high incidence and low reporting limits accurate surveillance, weakens institutional responses, and delays the development of effective prevention strategies. Objective: To identify the reasons behind the low reporting rate of WPV among health workers, especially nurses Design: Literature review. Data Sources: Scopus, Google Scholar, and Taylor & Francis databases were searched using the keywords “Workplace Violence,” “Healthcare Workers,” and “Nurses.” Review Process: Inclusion criteria comprised articles that discussed WPV prevalence and reporting behaviors and dated from 2020 onward. Screening of titles, abstracts, and full texts was performed, followed by detailed analysis of eligible studies. Results: Eleven studies from 10 Asian countries were included, with sample sizes ranging from 11 participants in a qualitative study to more than 20,000 registered nurses. Across settings, workplace violence was widespread, with prevalence rates ranging from 13.6% to nearly 90%. Despite this high occurrence, reporting remained limited. Personal barriers to reporting included fear of negative consequences, shame, guilt, and the perception that violence is an unavoidable part of nursing practice. Organizational barriers included unclear or inconvenient reporting procedures, lack of training, absence of system privacy, limited managerial support, and mistrust in reporting mechanisms. Collectively, these factors reinforced underreporting and contributed to unsafe work environments for nurses. Conclusion: Underreporting of WPV among nurses persists due to both individual and organizational barriers. Addressing this issue requires supportive reporting systems, training on WPV management, and fostering a non-punitive safety culture. Without targeted interventions, unsafe work environments will persist, compromising both nurse well-being and quality of patient care.